Library and Information (LIS) Research Topics in Indonesia from 2006 to 2017 - Nove Eka Variant Anna, NOVE (University of Nebraska-Lincoln, 2018)
Library and information research (LIS) has grown significantly asmore and more library and information science programs were established. The oldest LIS program in Indonesia is the Library and Information Department at the University of Indonesia (DIP UI) which was established in 1942. Since then, LIS at University of Indonesia has become a barometer for many other LIS programs in Indonesia. Other reputable LIS programs are Library & Information Science (JIIP) at Padjadjaran University, Department of Information and Library (DIIP) at Universitas Airlangga, and Library and Information Science at Diponegoro University, which are all located in big capital cities in Java Island. The development of LIS programs has a big contribution to the development of LIS research areas. Through their undergraduate theses and other scientific papers, LIS students have also had significant contributions to the development of LIS topics. Thesis is a compulsory unit for the bachelor degree in LIS in Indonesia, and so far there have been thousands of research in LIS conducted since the 1950s up to 2010s. However, there have not been many papers discussing the research trends in LIS in Indonesia. The aim of this chapter is to investigate the LIS research trends in Indonesia from 2006 to 2017. We took 5 reputable universities in Indonesia that have LIS programs as the sample, namely Universitas Airlangga-Surabaya, Diponegoro University-Semarang, Padjadjaran University-Bandung, North Sumatera University-Medan, and the University of Indonesia-Jakarta. The research samples are undergraduate theses that are available online in the institutional repositories of those five universities. The popular student’s research topics are library and information resources, library and information services, information society, and information systems.